Assessment of African swine fever impact in Bulgaria with special focus on the East Balkan Swine - Lazzaro, Elena; Dimitrova, Dessislava; Doneva, Radostina; Guardone, Lisa; Cristalli, Alessandro; Crovato, Stefania; Goracci, Jacopo; Bergmann, Hannes; Menconi, Vasco; Angeloni, Giorgia (Frontiers in Veterinary Science, 2025)
African Swine Fever (ASF) represents a significant threat to global pig production, due to its high lethality rate and the ability of the African Swine Fever Virus (ASFV) to persist in wild boar populations and the environment. In areas where small-scale pig farming is an important economic activity and a diverse source of protein, the disease also significantly affects nutritional security, food sovereignty and self-sufficiency. This study, conducted in Bulgaria, investigated the impact of ASF on small-scale pig farmers and East Balkan Swine farmers. A mixed-methods approach was employed, combining semi-structured interviews (n = 30), structured questionnaires (n = 10), and discussions with relevant authorities (n = 7), including farmers, health authorities and local veterinarians. The results highlight the vulnerability of traditional pig farming methods, with a significant focus on the East Balkan Swine, the last native pig breed in Bulgaria, whose population has been heavily affected by the disease.